A new coupled energy system consisting of fuel cell, solar thermal collector, and organic Rankine cycle; Generation and storing of electrical energy. (June 2022) - Chen, Yuning; Feng, Li; Mansir, Ibrahim B.; Taghavi, Mohammad; Sharma, Kamal
Highlights: A solar-based energy system to generate electricity and hydrogen fuel is evaluated. Generated electricity is stored through the pumped hydro and compressed air cycle. System can generate 208.5 kWh/day of electricity and 1.1 kg/day of hydrogen fuel. A volume of 96 m 3 is required for storage system to store available energy. Three scenarios are suggested to configuration of the solar farm. Abstract: To meet the growing demand for energy in societies and cities, solar-driven integrated energy systems equipped with electricity storage technology can be promising, which can lead to sustainable development and overcome environmental challenges. The purpose of this paper is to introduce and evaluate a new energy generation and storage configuration that solar energy plays a key role in the production of energy and hydrogen fuel. In the energy generation section, the solar farm based on the parabolic trough solar collector (PTSC) convert sun's light energy into thermal energy. The useful heat is then transferred to the organic Rankine cycle (ORC) sub-cycle. There, electric current is generated during a Rankine vapor process. A fraction of the electrical energy obtained during this process is feed into an alkaline electrolyzer (AEL) to produce hydrogen fuel. In addition, the products of the water decomposition process are feed into a proton-exchange membrane fuel cell (PEMFC) stack to generate heat and power. Also, a thermoelectric generator (TEG) is connected to the stack's exhaust so that it can generate additional electric current. The electric current obtained by the electricity production section is stored for later uses through the pumped hydro and compressed air (PHCA) cycle. The results indicated that the energy configuration can generate approximately 208.5 kWh/day of electrical energy. In addition, the electrolyzer can produce approximately 1.1 kg/day of hydrogen fuel from the water electrolysis process. Moreover, a volume of 96 m 3 is required for PHCA in order to store available energy. Based on the calculated number of PTSCs, three scenarios are suggested to configuration of the solar farm.